PROTECTION OF FREEDOMS THROUGH EMPLOYMENT RELATIONS AND HUMAN RIGHTS AND RULE OF LAW. FREEDOM TO WORK -& - THE RIGHT TO WORK - Skenderaj, Mallengjim (European Scientific Journal, ESJ, 2015)
Employment relations are integrable function of free societies and open democratic systems. In this context, they consist of two main pillars which are labor freedom and the right to work. Those are sanctioned freedoms and economical, social, cultural and Constitutional rights. Their quantitative and qualitative protection and development find legal immunity as well as, ethical and moral, through an organization, cooperation and unification union, creating the right social protection of labor, because all human life in its development and social progress is the foundation work which is closely connected to the right, with the right to life, the right to property, family law and Constitutional right. This value system should be developed in the free market labor through demand and supply that modern labor laws regulate a variety of substantive aspects of employment relations and general theories of employment in the progress of human welfare and progress.